Racial discrimination against prospective tenants : evidence from the room rental market in Singapore - Chew, Ilynn Mei Xian (Nanyang Technological University, 2020)
Results from past field experiments have converged in one direction — racial minorities experience significant discrimination in the room rental market. To investigate racial discrimination in Singapore, we conduct a correspondence study and create one fictitious Malaysian tenant profile for each race — Chinese, Malay, and Indian. Pioneering the use of instant messaging to respond to room rental advertisements, we gather message data from 408 listings and supplement it with landlord and flat characteristics from room viewings. Adapting Becker’s taste-based model to the rental market, we examine discrimination for room availability and rent. Our findings show that landlords have significant discrimination against minority races: On average, the Malay and Indian profiles are half as likely to receive positive responses for room availability than the Chinese profile. While discounts appear to be equal among different race profiles at the messaging stage, the Malay and Indian tenants are likely to have lower bargaining power for discounts than Chinese tenants at the viewing stage. These results suggest the need for interventions in the rental market before racial discrimination poses long-term negative consequences to Singapore.